Canine distemper virus phylogenetic structure and ecological correlates of infection in mesocarnivores across anthropogenic land use gradients - Jonathan Wilson; Samantha Rubio; Liliana C. M. Salvador; Nicole M. Nemeth; Jillian D. Fishburn; Nicole L. Gottdenker (Microbiology Spectrum)
ABSTRACT Anthropogenic land use impacts infectious diseases at the wildlife-domestic-human interface by changing host spatial distribution, behavior, density, and population dynamics. Canine distemper virus (CDV) is a significant cause of morbidity and mortality in many wild and domestic animals. Given the propensity of CDV to infect synanthropic mesocarnivores, it is important to investigate host and environmental factors affecting mesocarnivore CDV infection. Here, we investigated patterns of CDV infection and developed a statistical model to identify environmental variables related to CDV risk in commonly affected mesocarnivores. We sampled carcasses (N = 270) submitted to the Southeastern Cooperative Wildlife Disease Study from January 2019 to December 2022 and sequenced the CDV H-gene of 32 CDV-positive animals. Overall, 158 out of 270 mesocarnivores (58.5%) and four species (raccoon, red fox, gray fox, and striped skunk) were diagnosed with CDV across 13 states. Ripley’s K analysis showed positive cases were more spatially clustered at larger distances than expected due to chance. A generalized linear model for CDV-infected animals showed surface imperviousness, precipitation, and subadult/adult age classes were significant positive explanatory variables, but elevation had a significant negative association with CDV infection likelihood. H-gene sequence diversity among wild mesocarnivores in the southeastern United States was geographically separated into groups east and west of the Mississippi River, with only two eastern samples clustering with western groups. By identifying areas of intense human development at the highest risk for CDV, it may be possible to focus surveillance efforts in these areas, allowing for earlier outbreak identification, potentially preventing cross-species CDV transmission.IMPORTANCEAnthropogenic land use change can impact infectious disease spread by altering animal distribution and behavior. Canine distemper virus (CDV) is a significant cause of morbidity and mortality in wild and domestic carnivores. This study investigated how land use influences CDV infection in wild carnivores by examining tissues collected between 2019 and 2022 from wild carnivores found dead in the southeastern United States. CDV strains were geographically distinct, with differences between populations east and west of the Mississippi river. Statistical models showed areas with increased human development and higher precipitation had higher CDV risk; however, there was lower risk associated with higher elevations and younger animals. The importance of this study is that it identifies geographic structure of CDV in the southern United States, and identifies land-use associations with potential high-risk areas for CDV transmission-information that is useful for wildlife disease surveillance and control strategies.